2021
DOI: 10.3390/ma14092408
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Fibers for Sustainable Hybrid Fiber Cement Based Material: A Review

Abstract: Reinforcing fibers have been widely used to improve physical and mechanical properties of cement-based materials. Most fiber reinforced composites (FRC) involve the use of a single type of fiber to improve cement properties, such as strength or ductility. To additionally improve other parameters, hybridization is required. Another key challenge, in the construction industry, is the implementation of green and sustainable strategies based on reducing raw materials consumption, designing novel structures with en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 130 publications
(270 reference statements)
0
9
0
Order By: Relevance
“…Fibers of many different types are employed in concrete materials, including glass, steel, carbon, etc. [48][49][50][51][52]. Metal scrap, such as old steel parts, is a by-product of modern industry and is categorized as trash since it is produced inefficiently by machining.…”
Section: Usage Of Waste Plastic In Concretementioning
confidence: 99%
“…Fibers of many different types are employed in concrete materials, including glass, steel, carbon, etc. [48][49][50][51][52]. Metal scrap, such as old steel parts, is a by-product of modern industry and is categorized as trash since it is produced inefficiently by machining.…”
Section: Usage Of Waste Plastic In Concretementioning
confidence: 99%
“…A broad and arbitrary word, "workability of concrete" refers to how quickly freshly mixed concrete may be mixed, put, solidified and finished with little loss of homogeneity [1]. Fig 7 shows the average slump test result of the previous studies conducted on concrete infused with paper waste.…”
Section: Factors Influencing the Increment Of Compressive Strengthmentioning
confidence: 99%
“…Many decades ago, human civilizations were supported by cement-based materials. These materials have been adapted to keep their functions in our lives as human activities have progressed [1]. Cement's fundamental role is to act as a hydraulic binder, increasing the binding between fragmented particles and allowing them to be used in various industries [1].…”
Section: Introductionmentioning
confidence: 99%
“…These shortcomings limit the application of cement-based materials to a certain extent. In order to improve the shortcomings of cement-based materials and improve the application range, after a large number of experiments and studies by many scholars, it has been found that the mechanical properties and durability of composite materials have been significantly improved by adding fibers or nanomaterials to cement-based materials [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%